Racial/ethnic disparities in sleep duration and sleep disturbances among pregnant and non‐pregnant women in the United States. (29th February 2020) - Feinstein, Lydia; McWhorter, Ketrell L.; Gaston, Symielle A.; Troxel, Wendy M.; Sharkey, Katherine M.; Jackson, Chandra L.
Abstract: Sleep disturbances among pregnant women are increasingly linked to suboptimal maternal/birth outcomes. Few studies in the USA investigating sleep by pregnancy status have included racially/ethnically diverse populations, despite worsening disparities in adverse birth outcomes. Using a nationally representative sample of 71, 644 (2, 349 pregnant) women from the National Health Interview Survey (2004–2017), we investigated relationships between self‐reported pregnancy and six sleep characteristics stratified by race/ethnicity. We also examined associations between race/ethnicity and sleep stratified by pregnancy status. We used average marginal predictions from fitted logistic regression models to estimate prevalence ratios (PRs) and 95% confidence intervals (CIs) for each sleep dimension, adjusting for sociodemographic and health characteristics. Pregnant women were less likely than non‐pregnant women to report short sleep (PROverall  = 0.75; 95% CI, 0.68–0.82) and more likely to report long sleep (PROverall  = 2.06; 95% CI, 1.74–2.43) and trouble staying asleep (PROverall  = 1.34; 95% CI, 1.25–1.44). The association between pregnancy and sleep duration was less pronounced among women aged 35–49 years compared to those <35 years. Among white women, sleep medication use was less prevalent among pregnant compared to non‐pregnant women (PRWhite  = 0.45; 95% CI, 0.31–0.64), but this association was not observed among black women (PRBlack  = 0.98; 95% CI, 0.46–2.09) and was less pronounced among Hispanic/Latina women (PRHispanic/Latina  = 0.82; 95% CI, 0.38–1.77). Compared to pregnant white women, pregnant black women had a higher short sleep prevalence (PRBlack  = 1.35; 95% CI, 1.08–1.67). Given disparities in maternal/birth outcomes and sleep, expectant mothers (particularly racial/ethnic minorities) may need screening followed by treatment for sleep disturbances. Our findings should be interpreted in the historical and sociocultural context of the USA.